(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
It is proposed a nonlinear analytical model of the pivotal bond between the reinforcement and the concrete. It is established, that at the design of this process it is important to reach the level of engineering visibleness of the used dependences, dropping not essential features, while at the same time to get a reasonably accurate solution. In such search authors were stopped for the analytical model of nonlinear task of bond armature with a concrete, allowing to take into account elastic-plastic work of concrete, and also non-linearity of contact armature with a concrete. It is revealed that analytically the rod model of bond reinforced concrete bar is designed by the system, consisting of four equalizations, two from which are differential equalizations of first order. Nonlinear contact interaction of two materials is approximately examined as mutual relative displacements of armature and concrete. It is shown that the proposed model undoubtedly requires experimental confirmation by testing and numeral design more high level and degrees of working out in detail. Keywords: analytical model, bond armature with concrete, reinforced concrete constructions, physical nonlinearity, mutual relative displacement of reinforcement and concrete.